2013
DOI: 10.1021/bi301686a
|View full text |Cite
|
Sign up to set email alerts
|

Amyloids and Yeast Prion Biology

Abstract: The prions (infectious proteins) of Saccharomyces cerevisiae are proteins acting as genes, by templating their conformation from one molecule to another in analogy to DNA templating its sequence. Most yeast prions are amyloid forms of normally soluble proteins, and a single protein sequence can have any of several self-propagating forms (called prion strains or variants), analogous to the different possible alleles of a DNA gene. A central issue in prion biology is the structural basis of this conformational t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 189 publications
1
52
1
Order By: Relevance
“…59). Although the deletion or overexpression of any of several genes cures yeast prions, the Btn2/Cur1 system may be unique in curing prions at their normal levels.…”
Section: Discussionmentioning
confidence: 99%
“…59). Although the deletion or overexpression of any of several genes cures yeast prions, the Btn2/Cur1 system may be unique in curing prions at their normal levels.…”
Section: Discussionmentioning
confidence: 99%
“…7). Amyloids have also been identified in lower eukaryotes such as the budding yeast Saccharomyces cerevisiae, where they have been proposed to be pathological (8,9). This, however, is controversial, and others have suggested that S. cerevisiae may use amyloids to generate phenotypic diversity, thus allowing it to adapt to environmental stress (10,11).…”
mentioning
confidence: 99%
“…Such a mechanism is necessary to explain the rather stable inheritance of prion variant characteristics. The architecture of the yeast prion amyloid naturally suggests a mechanism that can explain this templating (7,127) (Fig. 4).…”
Section: In-register Parallel Folded Architecture Explains Conformatimentioning
confidence: 99%